KOMPETENSI PENELITIAN GURU: HARAPAN DAN KENYATAAN - Hastuti, Ayu Dwi; ., Sudiyanto; Octoria, Dini (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe objective of this research is to investigate the teachersâ levels of competencies in research on Ac-counting learning at Vocational High Schools of Surakarta, which include: (1) the teachersâ knowledge competencies in research; (2) the teachersâ attitude competencies in research; and (3) the teachersâ skill competencies in research. This research used the descriptive quantitative method with the survey re-search approach.The results of research are as follows: 1) The score of the teachersâ knowledge compe-tencies in research on Accounting learning at Vocational High Schools of Surakarta was 43.93, which belonged to the less good category, and there was not any tendency of difference in the teachersâ knowledge competencies in research due to the factors of gender, level of education, relevance of educa-tion, and teaching experience. 2) The score of the teachersâ attitude competencies in research on Ac-counting learning at Vocational High Schools of Surakarta was 75.68, which belonged to the fairly good category, and there was a tendency that the teachers were females, had the educational levels of Masterâs Degree Program and Diploma 3 Program, did not major in Accounting, had the teaching experience of 6-10 years, and had better competencies. 3) The score of the teachersâ skill competencies in research on Accounting learning at Vocational High School was 5.43, which belonged to the less good category, and there was not any tendency of difference in the teachersâ skill competencies due to the factors of gender, level of education, relevance of education, and teaching experience. The conclusions of this research is the teachersâ competency in research level on accounting learning at Vocational High Schools of Sura-karta in 2016 is less good.Keywords: Teachersâ competencies, research, Accounting learningABSTRAKPenelitian ini bertujuan untuk mengetahui (1) kompetensi pengetahuan guru tentang penelitian pada pembelajaran akuntansi; (2) kompetensi sikap guru terhadap penelitian pada pembelajaran akuntansi; (3) kompetensi keterampilan guru dalam penelitian pada pembelajaran akuntansi. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan teknik survei. Hasil penelitian menunjukkan bahwa: (1) kompeten-si pengetahuan guru tentang penelitian pada pembelajaran akuntansi di SMK Surakarta sebesar 43,93 (skala 100) termasuk dalam kategori kurang baik dan tidak terdapat kecenderungan perbedaan kompetensi pengetahuan guru dalam penelitian disebabkan faktor jenis kelamin, tingkat pendidikan, relevansi pen-didikan, dan pengalaman mengajar. (2) kompetensi sikap guru terhadap penelitian pada pembelajaran akuntansi di SMK Surakarta sebesar 75,68 (skala 100) termasuk dalam kategori cukup baik dan terdapat kecenderungan bahwa guru yang berjenis kelamin perempuan, mempunyai tingkat pendidikan S2 dan D3, bukan berasal dari pendidikan akuntansi, dan mempunyai pengalaman mengajar antara 6-10 tahun mempunyai kompetensi yang lebih baik (3) kompetensi keterampilan guru dalam penelitian pada pem-belajaran akuntansi di SMK Surakarta sebesar 5,43 (skala 100) termasuk dalam kategori kurang baik dan tidak terdapat kecenderungan perbedaan kompetensi keterampilan guru dalam penelitian disebabkan kare-na faktor jenis kelamin, tingkat pendidikan, relevansi pendidikan, dan pengalaman mengajar. Simpulan dalam penelitian ini adalah tingkat kompetensi guru dalam penelitian pada pembelajaran akuntansi di SMK Surakarta tahun 2016 adalah kurang baik.Kata kunci : Kompetensi Guru, Penelitian, Pembelajaran Akuntansi